PAIR: the remote industrial automation trainer - Silva, Mário (2015)
This paper presents the project PAIR Remote Industrial Automation Trainer. Its goal is to provide an environment where learners can improve their skills in Industrial Automation and practice their theoretical knowledge. In order to achieve this, PAIR will allow the users to explore automation concepts in some real scenes, as the control of an intelligent house or an industrial process. PAIR will also allow simulated virtual experiences associated to the real world scenarios.